Associations between cochlear electrophysiology, emotional health, and sleep quality in adults with tinnitus: a comprehensive analysis - Liu, Ye; Bao, Lihao; Mao, Xiaojiong; Shao, Kaixing; Xia, Guihua; Liu, Shaosheng; Ji, Ke (Frontiers in Psychiatry, 2026)
IntroductionTinnitus is commonly accompanied by emotional distress and sleep disturbances, yet the extent to which these characteristics relate to cochlear electrophysiologic findings remains unclear. This study examined associations between electrophysiologic measures and emotional and sleep parameters in adults with subjective tinnitus.MethodsThis retrospective study included 120 adults with tinnitus. Data collected included demographics, cochlear electrophysiologic measures (electrocochleography and auditory brainstem response), emotional characteristics (perceived stress, depressive symptoms, anxiety, emotion regulation), and sleep parameters (sleep quality, insomnia severity, daytime sleepiness). Correlation analyses and multivariate regression models were applied.ResultsThe mean age of the cohort was 62.35 years (SD 9.45), and 64.17% were male. A very weak negative correlation was observed between depressive symptoms and Wave III latency (r = –0.196, P = 0.03), but the small magnitude suggests minimal explanatory value. The summating potential/action potential ratio was not significantly correlated with sleep quality (r = –0.181, P = 0.05). In multivariate models, anxiolytic use was associated with a lower risk of poor sleep (adjusted odds ratio [aOR] = 0.262; 95% confidence interval [CI]: 0.078–0.881; P = 0.030), whereas antidepressant use was associated with a higher risk (aOR = 2.628; 95% CI: 1.027–6.724; P = 0.044). For insomnia, higher pure-tone average thresholds (aOR = 0.948 per dB; 95% CI: 0.906–0.992; P = 0.007) and hearing aid use (aOR = 3.396; 95% CI: 1.085–10.623; P = 0.036) were significant determinants. The only significant factor associated with quality of life was tinnitus duration, with longer duration associated with lower WHOQOL-BREF scores (β = –2.74; P = 0.020). No electrophysiologic parameter demonstrated significant associations in the multivariate models.ConclusionWithin the constraints of this study, cochlear electrophysiologic measures showed limited observable associations with emotional or sleep characteristics. Factors related to hearing status and medication use demonstrated stronger statistical associations with sleep outcomes, while tinnitus duration was linked to quality-of-life scores. These findings contribute to the growing body of descriptive evidence on tinnitus-related characteristics, although further research with larger cohorts and longitudinal designs is needed to clarify these relationships.